Dynamical and Trace Gas Responses of the Quasi‐Biennial Oscillation to Increased CO2. Issue 6 (22nd March 2021) - DallaSanta, K.; Orbe, C.; Rind, D.; Nazarenko, L.; Jonas, J.
Abstract: Long‐term projections of the Quasi‐Biennial Oscillation (QBO) remain uncertain. Using the high‐top "Middle Atmosphere" (MA) version of the NASA Goddard Institute for Space Studies (GISS) ModelE (E2.2‐AP), we show that increased CO2 reduces the QBO period and weakens its amplitude, consistent with results from recent multimodel studies. The amplitude response is asymmetric, with the easterly phase weakening more than the westerly phase. Results from both coupled atmosphere‐ocean and climatologically fixed sea surface temperature simulations link the period response to changes in parameterized convective gravity wave fluxes, whereas the amplitude changes are more closely tied to changes in tropical upwelling. Comparisons of simulations with and without ozone‐dynamical feedbacks reveal that ozone feedbacks increase the QBO amplitude and period in pre‐industrial control simulations, and reduce the response of the amplitude to increased CO2 . The response of stratospheric tracers to projected changes in the QBO is also investigated. Similarity between results using fully interactive (trace gas and aerosol) versus linearized ozone chemical mechanisms suggests that the QBO response to CO2 does not depend on additional chemical feedbacks beyond those associated with ozone, which implies that projected QBO changes may be credibly represented using simplified stratospheric ozone schemes. Key Points: In the NASA GISS Model E2.2‐AP, increased CO2 decreases QBO amplitude and period Amplitude/period changes are qualitatively linked to upwelling/convection changes, respectively Ozone feedbacks dampen the QBO amplitude response to increased CO2